Efficacy of a dip slide test for mutans streptococci in caries risk assessment - Pinelli C, Serra MC, Loffredo LCM (Blackwell Synergy, 2001)
The aim of this study was to evaluate the efficacy of a dip slide test for mutans streptococci in caries risk assessment, when the microbiological results were compared to well-defined clinical criteria (DCC) for caries risk, clinically measured through high and low caries activity.